Subclinical epileptiform activity during sleep in Alzheimer's disease and mild cognitive impairment - Brunetti, Valerio; D'Atri, Aurora; Della Marca, Giacomo; Vollono, Catello; Marra, Camillo; Vita, Maria Gabriella; Scarpelli, Serena; De Gennaro, Luigi; Rossini, Paolo Maria (Clinical neurophysiology, 2020)
•Patients with late-onset Alzheimer’s Disease (AD) do not show a higher-than-normal subclinical epileptiform activity.•Epileptiform activity during sleep is not prevalent in patients with late-onset AD and MCI due to AD.•Further studies are needed to define an approach to identify epileptiform activity in AD. Recent findings suggested that subclinical epileptiform activity is prevalent during sleep in a significant proportion of Alzheimer’s Disease (AD) patients. The aims of our study were: (A) comparing the frequency of subclinical epileptiform activity during the sleep in a sample diagnosed with ‘probable’ AD and Mild Cognitive Impairment (MCI) due to AD, and in healthy subjects; (B) evaluating epileptiform EEG activity as a function of different sleep stages within a well-controlled polysomnographic setting. We prospectively enrolled 50 ‘probable’ AD patients (73 ± 7.0 years) and 50 subjects with MCI due to AD (72 ± 6.7 years) without history of seizures, comparing them with 50 controls (69 ± 6.7 years). Patients underwent to a full-night video-PSG. Subclinical epileptiform activity was detected in 6.38% of ‘probable’ AD patients, 11.63% of MCI due to AD subjects and 4.54% of controls (p = 0.43). The comparisons between the three groups for the frequency of epileptiform activity did not reach statistically significant differences neither for total sleep nor for any sleep period considered. Our study shows that, when controlling for sleep stages and the influence of psychoactive drugs, AD patients and MCI due to AD subjects do not exhibit a higher frequency of epileptiform discharges during sleep compared to healthy subjects. Subclinical epileptiform activity during sleep does not discriminate ‘probable’ AD from MCI due to AD and healthy controls.